A QUALITATIVE RESEARCH OF WOMAN PERCEPTION OF GOLD JEWELRY AS INVESTMENT IN MANADO - Rompas, Prichillia Lavenia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Gold Jewelry is a type of gold is most frequently encountered in everyday life. For every purchase of Gold Jewelry, in addition to the gold price is calculated based on weight and rust, also be charged for the processing of gold into jewelry. When reselling gold, stores usually do not want to pay the cost of the jewelry making. Many of the people who still believe that investing in gold will provide benefits. Gold Jewelry is a basic form of gold investment that has been made by the people of Indonesia since the first This research designed to find out the woman perception of Gold Jewelry as investment in Manado. Theory related research are consumer perception and investment. The data was collected from 10 informants that every informants have different background and have different perception. This research is qualitative research that uses interview gather data. Result and conclusion is there are several categorization woman opinion that makes the customers choose to make Gold Jewelry as their investment such as Value, Lifestyle, and Decision Making. Therefore, the woman looking for more information about the right way to invest in gold. The Gold Jewelry has many disadvantages if made as an investment. So that with have sufficient knowledge the woman can change their investment from Gold Jewelry to gold bar or gold coin and in the end the women can get more profit. Keyword: woman perception, investment, gold jewelry